PROBLEMS OF DEVELOPMENT OF PROFESSIONAL TEACHER EDUCATION - N. M. Alexandrova; S. M. Markov (Вестник Мининского университета, 2017)
This article discusses the methodological and theoretical problems of vocational teacher education. These include: ensuring the processes of socialization and professionalization of the teacher of vocational training; actualization culturogical direction of professional teacher education; implementation of the system and predictive approaches to the educational process; spiritual development of the individual; as well as the problem of studying vocational educational processes on the basis of social, educational, integrative and comprehensive approaches. These include: the creation of new types of educational institutions; training in integrated groups of occupations; inclusion of retraining and advanced training of specialists, providing employment and employment in the vocational and teacher education; provision of training through research and scientific and industrial activities; functioning integrative educational system and modular control systems vocational teacher education.